Toward the recovery of common sense in a post-critical intellectual ethos - Cannon, Dale (Hervormde teologiese studies, 1993)
This article attempts to articulate what philosopherscientist Michael Polanyi meant by a post-critical intellectual ethos and to explore its implications for concrete academic practice. The modern critical tradition’s strategy for defeating the demon of self-doubt and for securing certainty, as Hannah Arendt has written, restricts serious candidates for belief to those whose conditions of truth can be rendered wholly immanent to focal consciousness within a point of view that is simply taken for granted. Thereby it forecloses the possibility of recognizing the partiality of its own perspective vis-á-vis that of others, taking into account the relevant perspectives of other persons, and reaching any kind of sense in common between perspectives. The institutionalization of this strategy in 20th century academic life is amply and insightfully documented in Bruce Wilshire’s Moral Collapse of the University. Michael Polanyi, in his writings, adumbrates a post-critical intellectual ethos in which the making of sense in common between persons of differing perspective is central to the enterprise of teaching, learning, and research.